The Process of Creating and Publishing Paintings: Case Study of the King Bhumibol Adulyadej Memorial Paintings Created and Published between October 2016 and June 2016 - ฉายะเจริญ สุริยะ (Siam Communication Review, 2017)
This article describes the process of producing and distributing paintings. The purpose is to convey the meaning of His Majesty King Bhumibol Adulyadej. To express the mournfulness and remembrance of His Majesty the King on his death on 13 October 2016, and to produce and disseminate public works in the form of creative works. The result of this work is the creation of 13 paintings produced by four techniques of painting. The creative work is a transition from photo to painting as a representation of the meaning of the King Bhumibol Adulyadej. There are three types of connotations : (1) the representation of monarchs dedicated to working for the people of Thailand and Thailand. (2) The representation of the reigning monarch for the succession of the Chakri Dynasty. (3) The representation of modern kings that center the soul of the nation. The painting has been publicized in 4 channels: Art Exhibition, Print media and online.